Circular cities: the case of Singapore. Issue 4 (17th July 2020) - Carrière, Sann; Weigend Rodríguez, Ricardo; Pey, Peixun; Pomponi, Francesco; Ramakrishna, Seeram
Abstract : Purpose: Circular economy (CE), as a new economic paradigm, has gained traction in recent years. Cities' role in driving CE forward has been perceived as being increasingly important to achieve sustainable development (SD). For this reason, there is an urgency to understand what a circular city is and how it might be composed. This research explores the ways in which the city-state of Singapore is transitioning to a CE. Design/methodology/approach: A systematic literature review on CE and cities was carried out using a bibliometric review and a snowballing technique. This review was performed on academic and on non-academic papers. Findings: This research has confirmed the lack of robust circular cities case studies. As Singapore has already begun its journey towards circularity, this article examines its current efforts and offers recommendations in the design and implementation of CE policies that may be valuable not just for Singapore but also for high-density and rapidly expanding cities around the world that require a new development pathway to emulate. Originality/value: This manuscript is the first detailed, independent and comprehensive review of Singapore's approach to CE.